PERAN KELOMPOK TANI DALAM MENINGKATKAN HASIL PANEN PADI DI DESA PAENRE LOMPOE KABUPATEN BULUKUMBA - Erwin Risal; Muh. Said; Shasliani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to: (1) describe the general condition of farmer groups in Paenre Lompoe Village, Bulukumba Regency; (2) analyze the role of farmer groups in improving rice production in Paenre Lompoe Village, Bulukumba Regency; and (3) identify the constraints encountered by rice farmers in Paenre Lompoe Village, Bulukumba Regency, as well as examine the extent to which farmer groups contribute to overcoming these constraints. The study applies a descriptive qualitative research design. Data were obtained through direct observation, in-depth interviews, and documentation. The data analysis process involved data reduction, data presentation, and the formulation of conclusions. The findings indicate that: (1) farmer groups in Paenre Lompoe Village, Bulukumba Regency are well-structured, with clear organizational arrangements and defined responsibilities; (2) farmer groups perform three key functions, namely as learning forums, cooperative institutions, and production units; and (3) the main challenges in increasing rice yields include limited availability of production inputs, pest and disease infestations, inadequate transportation facilities, and unpredictable climate and weather conditions. Overall, the results demonstrate that farmer groups in Paenre Lompoe Village play a significant and positive role in supporting the improvement of rice production.